The use of podcasts and videocasts by tertiary accounting students in distance education - Wentzel, L.; de Hart, K. (South African Journal of Higher Education, 2020)
Podcasts and videocasts are increasingly used in education, as they provide additional flexible learning resources to students. Research on the educational use and design of videocasts used by students in a distance education environment is, however, limited. In light of the need to ascertain how best to design videocasts, this article reports on distance students’ perceptions of using this technological innovation as part of teaching support provided by educators. The research was conducted by means of a survey and it investigated how videocasts were used by undergraduate students in a taxation module. The research also investigated the usefulness of videocasts to students in mastering the extensive content and complex principles. The results from this study found that students generally access the videocasts from home on a computer/laptop while working through or after reading the study unit. Most students reject the mobile aspect of videocasting and prefer to maintain their traditional study habits by watching each videocast at least once (or more than once for more difficult topics) during their focused study time. The majority of students perceive videocasting as having value, as this initiative provides them with additional support and helps them to understand the content more easily. It is evident that the use of videocasts as an additional learning tool in taxation distance education courses can enhance the learning experience of accounting students and it is a viable way of communicating content to and documenting processes for students to enable them to study more effectively.